Etyka e-sportu jako element wielopoziomowego systemu normatywnego = E-sports ethics as an element of a multi-level normativesystem - Stępnik, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to develop e-sports ethics as an element of a multi-level normative system, in which more specific norms would be derived from more general norms and theories developed in the field of general ethics. The author identifies unethical behaviors in e-sports, which should be regulated by moral norms. Such norms should be specified and included in the provisions of rules and regulations of e-sports competitions.The fair play principle is adopted as the basis for such regulation, fair play rules are specified in relation to e-sports, and possible justifications are provided. The author emphasizes the need to develop a variety of justifications, which will appeal to people at different levels of moral development, distinguished in Kohlberg?s theory.
Keywords: e-sport; etyka sportu; zasada fair play; teoria Kohlberga; e-sports; e-sports ethics; fair play principle; Kohlberg`s theory